ROBOTIC SYSTEM CONTROL - SRISKANDARAJAH, CHELLIAH; KUMAR, SUBODHA; RAMANAN, NATARAJAN (2004)
In an automated processing system, a system controller uses a meta-heuristic technique for identifying an optimal or near-optimal control schedule for controlling movements and operations of a robot. In particular embodiments, the system controller uses a genetic algorithm to breed a control schedule for the robot. In particular embodiments, the system controller dynamically updates the control schedule based on system operation.